Financial Literacy and Money Script A Caribbean Perspective - Sahadeo, Christine (Springer International Publishing, 2018)
Since the financial crisis, everyone is more aware of the need to be financially literate. This book covers a wide range of topics and assures the reader that understanding of one's money script and more particularly making changes (if necessary) would result in more effective and responsible managing and handling of one's financial affairs. It is a misnomer that graduates of tertiary education are financially literate or are qualified to make financial decisions. In fact, they are particularly vulnerable in making poor financial decisions as many students do not undertake courses in financial education and they therefore have limited financial knowledge. Training in financial literacy through university-based financial education programs is one method of addressing personal finances and financial stress among students. This book presents the key components of financial education designed to address the growing concerns associated with high levels of debt, abuse of credit cards, home ownership, savings and investments, risk management, and retirement. The chapters on entrepreneurship and business planning provide a roadmap for successful new ventures. The book is an excellent resource for students, those interested in developing or enhancing their understanding of money matters and financial wellbeing, and trainers involved in financial education, counseling, and planning.